FAKTOR PERSONALITAS DAN SOSIOKULTURAL DALAM PEMBELAJARAN BAHASA - FAJAR ASWATI (Pendidikan Bahasa dan Sastra Indonesia, 2019)
Learning languages ​​is a long and sustainable work. This certainly involves several aspects, both intellectual aspects, physical responses, and emotional aspects. Personality or personality in a person is a factor that can help the success and success of the language learning process. A person's personality plays an important role in the process of sending and receiving messages through language. This means that personality will determine the success of the second language acceptance. Culture is an integral part of the interaction between language and mind. Social and cultural or cultural factors have a very close relationship with language learning. Every time we teach one language, we also teach an entire system of cultural habits, values, ways of thinking, feeling, and acting. This problem will be answered in this paper using library research (library reaserch) which will answer any personality and sociocultural factors that can affect the language learning process. Data collected from various references; both primary, secondary and supporting data.